Power Management in DC Microgrids Using Hierarchical Control - Shipra Jain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
This paper suggests voltage control and power management scheme for a dc microgrid. A microgrid integrates a number of distributed energy sources and can be operated in islanded and grid connected modes. DC microgrids have a number of advantages as compared to AC microgrids because of their higher efficiency, stability and reliability. DC microgrids are prevalent because they are compatible with PV panels, batteries and dc loads. Different dc sources are co-ordinated using hierarchical control. The bus voltage is a measure of any unbalance between supply and demand. A hierarchical control scheme is suggested for the failsafe performance of the grid. A tradeoff between maximum power harvest and essential battery management is there in this control technique. To verify the results, proposed microgrid is implemented in MATLAB.